(untitled) (Journal of Student Affairs in Africa, 2026)
Student engagement includes both the actions of students and the practices of institutions. Learning communities (LCs) are educational programmes that combine both curricular and co-curricular experiences for students and serve as a way to increase participation in high-impact practices to boost engagement and help students transition into university. This reflective case study offers a framework to enhance student engagement by providing targeted support strategies through the Central Academic Advising Learning Communities (CAALC) project at the University of the Free State (UFS). The article shows how themes of student engagement, supported by Astin’s Student Involvement Theory (SIT), were used to develop the said project for undergraduate students. Between 2022 and 2023, a total of 2,129 students from the residential communities and 927 students from the curricular and student-type communities participated in all the project initiatives. Residential communities are on-campus housing arrangements, where students enrolled in two or more shared programmes reside closely together. In contrast, curricular and student-type communities are tailored for specific groups, such as students who are co-enrolled in multiple courses (often from different fields) unified by a common theme, such as students with disabilities, commuter students, probationary students, and so forth. In the first two years of the project’s implementation, participation trends and feedback were collected at the end of each year, with the students’ voices informing the strategy for the following year. The results indicated that student behaviour, sense of belonging and peer support, learning outcomes, and institutional support influence students’ level of engagement in learning. The study recommends a framework that potentially enhances institutional perspectives on student engagement and could be used to support the creation of environments more conducive to learning and fostering a sense of belonging through intentionally designed initiatives and the sharing of effective, evidence-based practices.